Use of the FebriDx point-of-care test for the exclusion of SARS-CoV-2 diagnosis in a population with acute respiratory infection during the second (COVID-19) wave in Italy. (July 2021) - Lagi, Filippo; Trevisan, Sasha; Piccica, Matteo; Graziani, Lucia; Basile, Gregorio; Mencarini, Jessica; Borchi, Beatrice; Menicacci, Lorenzo; Vaudo, Micol; Scotti, Valentina; Fabbri, Alessia; Bandini, Giulia; et al.
Highlights: Alternative point-of-care test may help in suspected COVID-19 case classification. FebriDx differentiates viral from bacterial acute respiratory infection. FebriDx had a good concordance and high NPV compared to rt-PCR. FebriDx could be a reliable rule out test for SARS-CoV-2 in high prevalence setting. Abstract: Objective: Evaluate the real-world accuracy of Myxovirus resistance protein A (MxA) detected by the rapid, point-of-care FebriDx test during the second-wave pandemic in Italy in patients with acute respiratory infection (ARI) and a clinical suspicion of COVID-19. Design and methods: Prospective, observational, diagnostic accuracy study whereby hospitalized patients with ARI were consecutively enrolled in a single tertiary care center in Italy from August 1, 2020 to January 31, 2021. Results: COVID-19 was diagnosed in 136/200 (68.0%) patients and Non-COVID-19 was diagnosed in 64/200 (32.0%) patients. COVID-19 patients were younger and had a lower Charlson comorbidity index compared to Non-COVID-19 patients (p < 0.001). Concordance between FebriDx, MxA and rt-PCR for SARS-CoV-2 (gold standard) was good (k 0.93, 95% CI 0.87–0.99). Overall sensitivity and specificity were 97.8% [95% CI 93.7–99.5] and 95.3% [95% CI 86.9%–99.0%], respectively. FebriDx demonstrated a negative predictive value of 95.3% (95% CI 86.9–99.0) for an observed disease prevalence of 68%. Conclusions: FebriDx MxA showed high diagnostic accuracy to identify COVID-19 and could be considered as a real-time triage tool to streamline the management of suspected COVID-19 patients. FebriDx also detected bacterial etiology in Non-COVID-19 patients suggesting good performance to distinguish bacterial from viral respiratory infection.